Telerehabilitation Guidelines for Patients with Breast Cancer (Ukrainian Language Edition) - Oleksandr A. Vladymyrov; Tetiana V. Semykopna; Dmytro V. Vakulenko; Oksana V. Syvak; Mykola M. Budnyk (International Journal of Telerehabilitation)
The document covers current advancements in telerehabilitation, including regulatory frameworks, clinical aspects of postmastectomy pain syndrome, and the role of the International Classification of Functioning, Disability and Health in managing patients with breast cancer. It details the Telerehabilitation Platform, describing its structural and functional components, including software modules and administrative subsystems. The guidelines also outline methods for evaluating telerehabilitation effectiveness and discuss patient-centered telerehabilitation programs for various stages, from preoperative to long-term care. Nine appendices provide additional resources such as questionnaires, physical therapy programs, and equipment requirements.